(3GdadSaI heOGNd GdYed s - (3SdeGf(B, (3RjOGfs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2023)
(3jbOe gPG GdcJGH OQGSI Mhd EOGQI GdLhOI GdTGedI, hjLjH Yf CSFdI oJYJHQ GdJMOj GdCcHQ def jQjO Cf jcJnH hjHMnK aj EOGQI GdLhOI GdTGedI, hgj GdJMOj GdChSY CeGe CUMGH GdehGbY GdCeGejI hGdeSFhdjI GdbjGOjI GdEOGQjI, Hd EfgG GdJMOj GdCYeb aj bOQI GdJYGed eY eaQOGJ GdMjGI, GdeYjpf GdPj dG jfVH, hGdefLpe GdgGFd GdedjA HGdeYdheGJ hGdCZQGV hGdehGba GdJj ef TCfgG JWhjQ GdYed hGdGQJbGA Hg Ydi fMh JROGO ajg EfJGLjI GdYed hGdEfJGL YHQ JYHFI GdehGQO GdHTQjI hGdeGOjI hGSJKeGQgG HMSGHGJ LOjOI heHOYI, hGdcJGH gh GdLQRA GdChd hjbY aj SJI aUhd(B: ((3eaGgje hadSaGJ EOGQI GdLhOI GdTGedI, EOGQI GdLhOI GdTGedI(B: (3adSaI GdJNWjW hgfOSI GdJfXje, CHYGO heOGNd GdLhOI GdTGedI, EOGQI GdLhOI GdTGedI hESJQGJjLjGJ GdJUfjY hGdJShjb, JcGdja GdLhOI GdTGedI hGdJMSjf GdeSJeQ ddYedjGJ, hCfXeI EOGQI GdLhOI hGdebGjjS GdOhdjI(B).s
(3GdeQGLY U(B.291s
Keywords: (3EOGQI GdLhOI GdTGedIs